Enhancement of astrocytic gap junctions Connexin43 coupling can improve long‐term isoflurane anesthesia–mediated brain network abnormalities and cognitive impairment. (25th September 2022) - Dong, Rui; Lv, Pin; Han, Yuqiang; Jiang, Linhao; Wang, Zimo; Peng, Liangyu; Ma, Zhengliang; Xia, Tianjiao; Zhang, Bing; Gu, Xiaoping
Abstract: Aim: Astrocytes are connected by gap junctions Connexin43 (GJs‐Cx43) forming an extensive intercellular network and maintain brain homeostasis. Perioperative neurocognitive disorder (PND) occurs frequently after anesthesia/surgery and worsens patient outcome, but the neural circuit mechanisms remain unclear. This study aimed to determine the effects of the GJs‐Cx43–mediated astrocytic network on PND and ascertain the underlying neural circuit mechanism. Methods: Male C57BL/6 mice were treated with long‐term isoflurane exposure to construct a mouse model of PND. We also exposed primary mouse astrocytes to long‐term isoflurane exposure to simulate the conditions of in vivo cognitive dysfunction. Behavioral tests were performed using the Y‐maze and fear conditioning (FC) tests. Manganese‐enhanced magnetic resonance imaging (MEMRI) and resting‐state functional magnetic resonance imaging (rs‐fMRI) were used to investigate brain activity and functional connectivity. Western blot and flow cytometry analysis were used to assess protein expression. Results: Reconfiguring the astrocytic network by increasing GJs‐Cx43 expression can modulate 22 subregions affected by PND in three ways: reversed activation, reversed inhibition, and intensified activation. The brain functional connectivity analysis further suggests that PND is a brain network disorder that includes sleep‐wake rhythm–related brain regions, contextual and fear memory–related subregions, the hippocampal‐amygdala circuit, the septo‐hippocampal circuit, and the entorhinal‐hippocampal circuit. Notably, remodeling the astrocytic network by upregulation of GJs‐Cx43 can partially reverse the abnormalities in the above circuits. Pathophysiological degeneration in hippocampus is one of the primary hallmarks of PND pathology, and long‐term isoflurane anesthesia contributes to oxidative stress and neuroinflammation in the hippocampus. However, promoting the formation of GJs‐Cx43 ameliorated cognitive dysfunction induced by long‐term isoflurane anesthesia through the attenuation of oxidative stress in hippocampus. Conclusion: Enhancing GJs‐Cx43 coupling can improve brain network abnormalities and cognitive impairment induced by long‐term isoflurane anesthesia, its mechanisms might be associated with the regulation of oxidative stress and neuroinflammation. Abstract : Perioperative neurocognitive disorder (PND) is a brain network disorder that includes sleep‐wake rhythm–related brain regions, contextual and fear memory–related subregions, the hippocampal‐amygdala circuit, the septo‐hippocampal circuit, and the entorhinal‐hippocampal circuit. Increasing gap junctions Connexin43 (GJs‐Cx43) coupling could ameliorate the abnormal brain function network patterns induced by long‐term isoflurane anesthesia and contribute to the underlying neural circuits associated with PND.